Functional Development of Principal Neurons in the Anteroventral Cochlear Nucleus Extends Beyond Hearing Onset - Müller, Maria Katharina; Jovanovic, Sasa; Keine, Christian; Radulovic, Tamara; Rübsamen, Rudolf; Milenkovic, Ivan (Frontiers in Cellular Neuroscience, 2019)
Sound information is transduced into graded receptor potential by cochlear hair cells and encoded as discrete action potentials of auditory nerve fibers. In the cochlear nucleus, auditory nerve fibers convey this information through morphologically distinct synaptic terminals onto bushy (BCs) and stellate cells (SCs) for processing of different sound features. With expanding use of transgenic mouse models, it is increasingly important to understand the in vivo functional development of these neurons in mice. We characterized the maturation of spontaneous and acoustically evoked activity in BCs and SCs by acquiring single-unit juxtacellular recordings between hearing onset (P12) and young adulthood (P30) of anesthetized CBA/J mice. In both cell types, hearing sensitivity and characteristic frequency range are mostly adult-like by P14, consistent with rapid maturation of the auditory periphery. In BCs, however, some physiological features like maximal firing rate, dynamic range, temporal response properties, recovery from post-stimulus depression, first spike latency and encoding of sinusoid amplitude modulation undergo further maturation up to P18. In SCs, the development of excitatory responses is even more prolonged, indicated by a gradual increase in spontaneous and maximum firing rates up to P30. In the same cell type, broadly tuned acoustically evoked inhibition is immediately effective at hearing onset, covering the low- and high-frequency flanks of the excitatory response area. Together, these data suggest that maturation of auditory processing in the parallel ascending BC and SC streams engages distinct mechanisms at the first central synapses that may differently depend on the early auditory experience.